2021
DOI: 10.1080/14756366.2021.1919890
|View full text |Cite
|
Sign up to set email alerts
|

Phenyl-substituted aminomethylene-bisphosphonates inhibit human P5C reductase and show antiproliferative activity against proline-hyperproducing tumour cells

Abstract: In certain cancers, such as breast, prostate and some lung and skin cancers, the gene for the enzyme catalysing the second and last step in proline synthesis, d 1 -pyrroline-5-carboxylate (P5C) reductase, has been found upregulated. This leads to a higher proline content that exacerbates the effects of the so-called proline-P5C cycle, with tumour cells effectively using this method to increase cell survival. If a method of reducing or inhibiting P5C reductase could be discovered, it would provide new means of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…These are published reports of inhibitors of the proline regulated axis and its downstream effectors (D'Aniello et al 2020 ). A recent report identified Phenyl-substituted aminomethylene bisphonates as inhibitors of human P5C reductase and antiproliferative activity in tumor cells (Forlani et al 2021 ). Hopefully, many others will emerge and future clinical trials especially as adjuncts for chemotherapy drugs may lead to novel therapies.…”
Section: Proline Metabolism and Cancermentioning
confidence: 99%
“…These are published reports of inhibitors of the proline regulated axis and its downstream effectors (D'Aniello et al 2020 ). A recent report identified Phenyl-substituted aminomethylene bisphonates as inhibitors of human P5C reductase and antiproliferative activity in tumor cells (Forlani et al 2021 ). Hopefully, many others will emerge and future clinical trials especially as adjuncts for chemotherapy drugs may lead to novel therapies.…”
Section: Proline Metabolism and Cancermentioning
confidence: 99%
“…Mice were sensitized with PVM-OVA, PVM-OVA followed by BPTES or NFLP, or PVM-OVA followed by BPTES+Proline or NFLP +Proline, and challenged with OVA after 21 days post infection. PYCR1 was obviously reduced in PVM-OVA group, compared with that in PBS group (Figure 4E, P<0.05), which may be due to feedback inhibition of increased proline (32). All of the data suggested that proline synthesis pathway is remarkably active in PVM-OVA group.…”
Section: Proline Metabolism In Mice Sensitized With Pvm-ova Was Signi...mentioning
confidence: 79%
“…The relative expression of GLS1 or GLS2 significantly increased in PVM-OVA group, compared with that in PBS group, which was consistent with the change of proline ( Figure 4E , P<0.05). However, the expression of PYCR1 was obviously reduced in PVM-OVA group, compared with that in PBS group ( Figure 4E , P<0.05), which may be due to feedback inhibition of increased proline ( 32 ). All of the data suggested that proline synthesis pathway is remarkably active in PVM-OVA group.…”
Section: Resultsmentioning
confidence: 94%
“…Likewise, up-regulation of L-Pro biosynthesis genes (ALDH18A1 and PYCR1) also reveals L-Pro starvation in tumor cells (D'Aniello et al, 2020). Moreover, ALDH18A1 knock-down activates AAR stress signaling, and reduces melanoma tumor growth both in vitro and in vivo (Kardos et al, 2015), whereas PYCR1 induction improves proliferation and invasiveness of breast, esophagus, lung, melanoma, pancreas, and prostate cancer cells (Nilsson et al, 2014;Ding et al, 2017;Zeng et al, 2017;Cai et al, 2018;Ye et al, 2018;Kardos et al, 2020;Forlani et al, 2021). Of note, kindlerin 2 (KINDLING-2) protein stabilizes the mitochondrial PYCR1 enzyme, increasing L-Pro synthesis and lung adenocarcinoma cell proliferation (Guo et al, 2019).…”
Section: Cancer Cellsmentioning
confidence: 99%